Coordination qualities rating technologies applicable for young sports prospects selection - Botyaev, V. L.; Botyaev, S. V.; Tulaev, V. K.; Apokin, V. V.; Losev , V. Yu. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to develop, on a sound theoretical basis, and test benefits of a new coordination qualities rating model for objective sport selections of young prospects.